2017
DOI: 10.1101/184499
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Elucidation of the 14-3-3ζ interactome reveals critical roles of RNA splicing factors during adipogenesis

Abstract: Adipogenesis is facilitated by a complex signaling network requiring strict temporal and spatial organization of effector molecules. Molecular scaffolds, such as 14-3-3 proteins, coordinate such events, and we have previously identified 14-3-3ζ as an essential scaffold in adipocyte differentiation. The interactome of 14-3-3ζ is large and diverse, and it is possible that novel adipogenic factors may be present within it. Mouse embryonic fibroblasts from mice over-expressing a TAP-epitope-tagged 14-3-3ζ molecule… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 60 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…We previously reported essential roles of one of the seven mammalian isoforms, 14-3-3ζ, in adipogenesis, as systemic deletion of 14-3-3z in mice resulted in significant reductions in visceral adipose tissue mass and decreased expression of mature adipocyte markers in gonadal adipocytes (34). Furthermore, through the use of proteomics to elucidate the 14-3-3z interactome, we found that 14-3-3z is necessary for RNA splicing during adipocyte differentiation (42). However, whether 14-3-3ζ can also influence metabolic processes specific to mature adipocytes has not been fully examined.…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…We previously reported essential roles of one of the seven mammalian isoforms, 14-3-3ζ, in adipogenesis, as systemic deletion of 14-3-3z in mice resulted in significant reductions in visceral adipose tissue mass and decreased expression of mature adipocyte markers in gonadal adipocytes (34). Furthermore, through the use of proteomics to elucidate the 14-3-3z interactome, we found that 14-3-3z is necessary for RNA splicing during adipocyte differentiation (42). However, whether 14-3-3ζ can also influence metabolic processes specific to mature adipocytes has not been fully examined.…”
Section: Introductionmentioning
confidence: 86%
“…3T3-L1 cells were maintained in DMEM (Life Technologies Corporation, Grand Island, NY), supplemented with 10% newborn calf serum (NBCS) and 1% penicillin/streptomycin (P/S) and were seeded onto 12-well plates (100,000 cells/well) or 10cm dishes (2x10 6 cells/dish) 2 days prior to the induction of differentiation. Confluent cells were treated with a differentiation cocktail (DMEM supplemented with 10% FBS, 1% P/S, 500 μM IBMX, 500 nM dexamethasone and 172 nM insulin) for 48 hours, followed by media replacement (DMEM with 10% FBS, 1% P/S and 172 nM insulin) every 2 days for 7-8 days (34,42). Knockdown and overexpression of 14-3-3ζ was achieved by transfecting day 7-8 differentiated cells with scrambled control siRNA, 14-3-3ζ-specific siRNA (Ambion, Austin, TX), GFP control plasmids, or plasmids encoding 14-3-3ζ (14-3-3ζ IRES-GFP) using the Amaxa Cell Line Nucleofector Kit L, as per manufacturer's instructions (Lonza, Koln, Germany).…”
Section: Cell Culture and Transient Transfectionsmentioning
confidence: 99%
See 3 more Smart Citations